Rising sea levels - Mattern, Joanne, 1963- (21st-century engineering solutions for climate change., 2019)
Explores the problems facing shore and beach communities with the rising sea levels found around the world. Includes modern ideas and innovations that could be used to save these fragile ecosystems.